Challenges, progress, and opportunities in clinical toxicology in Nepal: a narrative review - Rakesh Ghimire; Rajesh Sharma; Sangha Ratna Bajracharya; Manish Yadav; Ziad Kazzi; Bibhav Acharya; Michael Eddleston; Ramu Kharel (Toxicology Communications)
Toxicological emergencies pose a significant health burden in Nepal, particularly in rural agricultural regions. Intentional pesticide self-poisoning, especially with organophosphates, contribute heavily to this burden. This narrative review synthesizes the current state of toxicological care in Nepal, highlighting epidemiological data, educational programs, policy developments, and resource availability up to 2024. Despite hospital-based studies, aggregate data on toxicology care is lacking. Major barriers include insufficient trained human resources and limited access to antidotes and antivenoms. The review emphasizes the urgent need for formal clinical toxicology training, improved toxicological emergency management, and policy implementation to reduce the burden of poisoning in Nepal.